PLURALISME AGAMA DI INDONESIA: Tantangan dan Peluang Bagi Keutuhan Bangsa - Lestari, Julita (Al-Adyan: Journal of Religious Studies, 2020)
Diversity of religion on the one hand gave birth to segregate among the religious followers. On the other hand, uniting is driven by mutual respect for differences. This article studies the two side of these plurality in Indonesia as a state which is built from the diversity of religions. In Indonesia, plurality has twu potentials, namely opportunities and challenges for the national integrity. The biggest chllenge of this nation is the tendency of conflict which is derrived by the truth claim of each religious group. While, the opportuniy of plurality of the nation is tolerance of each religious followers for the integrity of the nation.Keberagaman agama di satu sisi cenderung melahirkan perpecahan di kalangan umat beragama. Di sisi lain persatuan yang didorong oleh sikap saling menghargai akan perbedaan yang ada. Artikel ini mengkaji kedua sisi pluralisme di Indonesia sebagai sebagai negara yang terbangun dari keragaman agama. Pluralitas agama di Indonesia memiliki tantangan dan peluang bagi keutuhan bangsa. Tantangan terbesar pluralitas bangsa ini adalah kecenderungan konflik yang bersumber dari truth claim (klaim kebenaran) masing-masing kelompok keagamaan. Sementara peluang pluralitas adalah sikap toleransi masing-masing penganut agama yang menopang keutuhan bangsa.